(3cJGH aj GdMLGeI hGdeHVYs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd LGdjfhS GSJNQLJ gPG ef cJH HbQGW ai GdMLGeI hGdeHVY hdGdYdb dEXgGQ GdefGaY ai LejY GdMSO s
(3BNQgG (B:s
(3HGH GdMLGeI HGdfGQ hEPG hVYJ GdMLGeI HGdSQI Ydi GdfGQ agi fGaYI ef QjGM GdHhGSjQ hddQjGM GdJi Mhd GdSQI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfi YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs